Participation in organizational networks and use of information and comunication technologies. An study about their impact on performance of comunidad valenciana co-operative schools - Campos Climent, Vanessa; Navarro Babiera, Cristina (REVESCO. Revista de Estudios Cooperativos, 2017)
Co-operative schools belong to one of the most unknown realities within the education system. These co-operatives go beyond to be a merely profitable entrepreneurial reality, appearing as an alternative educational model with clear transformational purposes. Co-operative schools are immerses in the educational system but propose a different educational offer from those other approaches that we can consider the traditional ones. For these reasons, it can be interesting to identify the factors that have an impact on the economic and social performance of such organizations. The current study purpose is to analyze the impact of the employ of ICTs and the participation in organizational networks, as support tools for co-operative schools management, on both economic and social performance. To this end we perform an empirical study based on a sample of 23 Valencian co-operative schools. Results show the existence of a significant positive impact of ITCs employment on economic performance, while it has not been possible to establish the existence of any kind of significant impact of ICTs on social performance. Research neither allows to identify any significant relationship between the participation in organizational networks and the co-operative schools performance, both economic and social performance.